Physician-Patient Communication from an Intercultural Perspective: An Exploratory Study in the United Arab Emirates - Gorpe, Tevhide Serra; Oksuz, Burcu; Allam, Hilda (Journal of Contemporary Issues in Media & Communication (JCIMC), 2025)
The objective of the study is to explore physician-patient communication in an intercultural context —the United Arab Emirates —through the experiences of physicians. The United Arab Emirates is among the most diverse populations globally. Intercultural communication competence is highly valued in diverse environments, and it is particularly significant in professions such as health care. The study aims to assess the intercultural competence skills of physicians through their encounters. To explore this, semi-structured interviews with physicians living and working in the United Arab Emirates are carried out. The findings of the qualitative study conclude that language is seen as either an obstacle or a facilitator. The importance of nonverbal language, the role of interpreters, and Google Translate have been highlighted in overcoming the language barrier. Language is considered a barrier because it blocks the passing of emotions. Experience in the medical field has been mentioned as an advantage for overcoming communication barriers. Knowledge about the cultural background is one of the dimensions that guides physicians in how to communicate. Other dimensions are the personality of the patient, age, and education. The physicians mentioned that they are aware of the sensitive issues and can easily modify their communication. Trust plays a crucial role in physician–patient communication. Physicians generally perceive themselves as good communicators, a quality considered particularly important in the UAE. Key aspects emphasized include listening, providing follow-up, and being accessible, with language identified as one of the most essential communication skills.